Effects of Gua Sha therapy on perimenopausal syndrome: A systematic review and meta-analysis of randomized controlled trials. (May 2018) - Ren, Qing; Yu, Xinyu; Liao, Fujiu; Chen, Xiaofan; Yan, Dongmei; Nie, Heyun; Fang, Jinju; Yang, Meng; Zhou, Xu
Abstract: Objective: In East Asia, Gua Sha therapy is widely used in patients with perimenopausal syndrome. The goal of this systematic review was to evaluate the available evidence from randomized controlled trials (RCTs) of Gua Sha therapy for the treatment of patients with perimenopausal syndrome. Methods: Databases searched from inception until June 2017 included: PubMed, Embase, the Cochrane Central Register of Controlled Trials and four Chinese databases [WanFang Med Database, Chinese BioMedical Database, Chinese WeiPu Database, and the China National Knowledge Infrastructure (CNKI)]. Only the RCTs related to the effects of Gua Sha therapy on perimenopausal syndrome were included in this systematic review. A quantitative analysis of RCTs was employed using RevMan 5.3 software. Study selection, data extraction, and validation were performed by two independent reviewers. Cochrane criteria for risk-of-bias were used to evaluate the methodological quality of the trials. Results: A total of 6 RCTs met the inclusion criteria, and most were of low methodological quality. When compared with Western medicine therapy alone, meta-analysis of 5 RCTs indicated favorable statistically significant effects of Gua Sha therapy plus Western medicine on the Kupperman Menopausal Index (KMI) Score [mean difference (MD) = -4.57, 95% confidence interval (CI) (−5.37, −3.77), p  < 0.01; heterogeneity: Chi 2  = 29.57 p  < 0.01, I 2  = 86%]. Moreover, study participants who received Gua Sha therapy plus Western medicine therapy showed significantly greater improvements in serum levels of follicle-stimulating hormone (FSH) [MD = −5.00, 95% CI (−9.60, −0.40), p  = 0.03], luteinizing hormone (LH) [MD = −4.00, 95% CI (−7.67, −0.33), p  = 0.03], and E2 [MD = −6.60, 95% CI (−12.32, −0.88), p  = 0.02] compared to participants in the Western medicine therapy group, with a low heterogeneity (Chi 2  = 0.12, p  = 0.94, I 2  = 0% in FSH; Chi 2  = 0.19 p  = 0.91, I 2  = 0% in LH; Chi 2  = 0.93, p  = 0.63, I 2  = 0% in E2 ). In addition, the pooled results displayed favorable significant effects of Gua Sha therapy plus the Western medicine therapy on the MENQOL scale when compared with the Western medicine therapy alone [MD = −5.13, 95% CI (−7.45, −2.81), p  < 0.01] with low heterogeneity (Chi 2  = 0.66, p = 0.42, I 2  = 0%). Conclusion: Preliminary evidence supported the hypothesis that Gua Sha therapy effectively improved the treatment efficacy in patients with perimenopausal syndrome. Additional studies will be required to elucidate optimal frequency and dosage of Gua Sha. Highlights: Gua sha therapy is an effective method to treat patients with PMS. The meta-analysis showed superior effects of Gua sha therapy on treatment efficacy and physical function.